Updated S3-Guideline Ulcerative Colitis. German Society for Digestive and Metabolic Diseases (DGVS) - Authors; Kucharzik, Torsten; Dignass, Axel U.; Atreya, Raja; Bokemeyer, Bernd; Esters, Philip; Herrlinger, Klaus; Kannengießer, Klaus; Kienle, Peter; Langhorst, Jost; Lügering, Andreas; Schreiber, Stefan; Stallmach, Andreas; Stein, Jürgen; Sturm, Andreas; Teich, Niels; Siegmund, Britta; Collaborators; Andus, T.; Autschbach, F.; Bachmann, O.; Baretton, G.; Baumgart, D. C.; Bettenworth, D.; Bläker, M.; Buderus, S.; Büning, J.; Ehehalt, R.; Fellermann, K.; Fichtner-Feigl, S.; Götz, M.; Gross, C.; Hartmann, F.; Hartmann, P.; In der Smitten, S.; Häuser, W.; Helwig, U.; Kaltz, B.; Kanbach, I.; Keller, K. M.; Klaus, J.; Koletzko, S.; Kroesen, A.; Kruis, W.; Kühbacher, T.; Leifeld, L.; Maaser, C.; Matthes, H.; Moog, G.; Ockenga, J.; Pace, A.; Reinshagen, M.; Rijcken, E.; Rogler, G.; Stange, E.; Veltkamp, C.; Zemke, J. (Zeitschrift für Gastroenterologie, 2019)
This guideline provides evidence-based key recommendations for diagnosis and treatment of ulcerative colitis and upgrades the 2011 version. The guideline was developed by an interdisciplinary team of gastroenterologists, surgeons, pathologists, nutrition experts, and patient support groups under the auspice of the German Society for Gastroenterology and Metabolic Diseases. The guideline used structural S3 consensus-based methodology and includes statements on clinical practice, prevention, infectiological problems, surgery and nutrition.
Keywords: ulcerative colitis; IBD; diagnosis; treatment; remission; maintenance